2009
DOI: 10.1103/physrevb.79.174415
|View full text |Cite
|
Sign up to set email alerts
|

Charge pumping and the colored thermal voltage noise in spin valves

Abstract: Spin pumping by a moving magnetization gives rise to an electric voltage over a spin valve. Thermal fluctuations of the magnetization manifest themselves as increased thermal voltage noise with absorption lines at the ferromagnetic resonance frequency and/or zero frequency. The effect depends on the magnetization configuration and can be of the same order of magnitude as the Johnson-Nyquist thermal noise. Measuring colored voltage noise is an alternative to ferromagnetic resonance experiments for nanoscale fer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…(14) is simply multiplied by cos 2 α [33], because only the z projection (cos α) of the fluctuating ISHE current [Eq. (10) …”
Section: Theorymentioning
confidence: 99%
“…(14) is simply multiplied by cos 2 α [33], because only the z projection (cos α) of the fluctuating ISHE current [Eq. (10) …”
Section: Theorymentioning
confidence: 99%
“…However, frequency-dependent, i.e., colored noise can contain interesting information on the system at hand. For example, in a recent paper Xiao et al [4] show that, via the mechanism of spin pumping [5], a thermally agitated spin valve emits noisy currents with a colored power spectrum. They show that the peaks in the spectrum coincide with the precession frequency of the free ferromagnet of the spin valve.…”
Section: Introductionmentioning
confidence: 99%
“…8 It has been shown that the noise in magnetic structures, such as spin valves, can be colored, i.e., it can have a nontrivial frequency dependence. 9 In diffusive metallic conductors colored noise has been observed experimentally, 10 however in magnetic structures it still requires further investigation.…”
Section: Introductionmentioning
confidence: 99%